PEMBERDAYAAN MASYARAKAT TERHADAP DAMPAK PEREDARAN NARKOTIKA DAN PERAN PEMUDA DALAM MEMINIMALISIR PEREDARAN NARKOTIKA DI KALANGAN REMAJA - Laode Muhamad Fathun; Nurmasari Situmeang; Hesti Rosdiana (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
This activity aims to explain and disseminate the consequences and circulation of illegal narcotics circulation and the role of youth. This activity also explains the factors that cause massive illegal narcotics trafficking in Indonesia. This activity was carried out at the Cilandak Branch of the Aisyah Orphanage Foundation in South Jakarta from May to November 2019. This activity took the form of socialization and discussion with the orphanage children and orphanage administrators. This activity involves lecturers and practitioners. This research describes the consequences of narcotics' excessive trafficking from various scientific perspectives such as social, political, legal, cultural, and economic. The result obtained is that children from orphanages are vulnerable to illegal drug trafficking. Life experience before entering an orphanage is a vulnerability for them to be contaminated. Thus, the researchers provided the orphanage children with the knowledge and formed a unit of anti-narcotics officers who functioned as informants in the event of irregularities in the illegal distribution of narcotics. Hopefully, this program can be expanded and increase the knowledge of many people so that narcotics will no longer threaten Indonesian society's stability and security.